Relations between the meaning of work, psychological well-being, and psychological distress: A study in the state military police in São Paulo, Brazil - Mendes, Fernando Edson (International journal of police science & management, 2024)
The state military police of the Brazilian state of São Paulo (PMESP) has the lowest number of police officers in the institution since the 1990s, compared to itself, with a vast number of unpaid leave and resignation requests. Low salaries appear to be a reason, but the police say that this is not the only factor to be rectified; lack of recognition and difficulties in overcoming trauma are also frequently mentioned. This picture refers to a situation that can be understood as low motivation, loss of meaning, and psychological suffering. This study aimed to understand whether there is a general loss of meaning at work in PMESP, together with well-being and psychological suffering. Using structural equation modeling, the study sought to understand the factors that give meaning to the work of these professionals and their consequences for well-being and psychological distress at work. Social usefulness and learning and development opportunities showed a meaningful relationship with meaning of work, with learning and development opportunities being the most important for the surveyed military police officers. Regarding the consequent constructs of meaning of work, significant relationships between psychological well-being at work and psychological suffering were verified. The study indicates that when meaning is constructed (via social utility and learning), there is an increase in psychological well-being, as well as a decrease in the effect of psychological suffering.